Mechanical properties, fracture morphology and thermal analysis of untreated and alkaline treated salago fiber epoxy laminated composites - Jerome D Lopena; Jeremiah C Millare (Materials Research Express, 2021)
Natural fibers gain acceptance in various applications due to their advantages over synthetic materials especially in terms of environmental impact, lightweight feature, availability and cost. Apparently, a natural fiber that still needs further exploration on its use in composite is salago. In this study, untreated and alkaline treated salago fiber with varying number of layers from one to three sheets were reinforced in epoxy resin. FTIR analysis and optical microscopy were used to analyze the effect of 5 wt. % sodium hydroxide treatment on the fiber sheets. On the other hand, the composites were subjected to tensile, flexural and Izod impact tests. Tensile fracture morphology was observed through FESEM while thermal degradation was evaluated using thermogravimetric-differential thermal analysis. As compared to neat epoxy, improvements on tensile (52.8%), flexural (37.6%) and impact (more than 6 times) strengths were obtained for the composite with three layers of untreated fiber sheets. Generally, the mechanical properties of the composites improved as the fiber sheets increases. However, the alkaline treated fiber composites obtained lower strengths than their untreated counterparts which may be associated to the presence of holes on the fiber sheets caused by the chemical treatment. Nevertheless, enhancements on moduli and thermal stability were still achieved for the composites with treated fibers which could be related to the good fiber-matrix adhesion caused by the partial removal of hemicellulose and lignin. Moreover, the composite can be used in applications that require high impact strength and stiffness like frame for drones or robots.